2020
DOI: 10.18502/ssu.v27i12.2835
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Effect of Breast-Milk and Leg Massage on Neonate’s Pain ‎Intensity during Heel-Blood Sampling in Neonatal Care Unit

Abstract: Introduction: Prevention and management of pain is one of the major challenges in the neonate intensive care units. The aim of this study was to evaluate the effect of breast-milk and leg massage on the intensity pain from painful procedures such as heel stick. Methods: This study was a randomized clinical trial aimed to compare the effect of breast-milk and leg massage on neonate’s pain intensity during heel-blood sampling in neonatal care unit of Tehran Fayazbakhsh Hospital, Iran in 2016. Neonates were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
6

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 0 publications
0
5
0
6
Order By: Relevance
“…From the 12 records included in this review, 11 are randomized clinical trials (24)(25)(27)(28)(29)(30)(31)(32)(33)(34)(35) , and one is characterized as a non-randomized clinical trial (26) , with a total of 981 participants and the age ranged between 24 hours of life and 42 weeks of Gestational age (GA). The characteristics of the study are summarized in Chart 2 (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…From the 12 records included in this review, 11 are randomized clinical trials (24)(25)(27)(28)(29)(30)(31)(32)(33)(34)(35) , and one is characterized as a non-randomized clinical trial (26) , with a total of 981 participants and the age ranged between 24 hours of life and 42 weeks of Gestational age (GA). The characteristics of the study are summarized in Chart 2 (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) .…”
Section: Resultsmentioning
confidence: 99%
“…As for the intervention technique, four (33.3%) studies reported the application of light to moderate pressure massage (26)(27)(28)30) and eight (66.6%) did not specify the pressure used during the massage (24)(25)29,(31)(32)(33)(34)(35) . Regarding the application time, six (50%) studies performed the massage for 2 minutes; three (25%) for 3 minutes; one (8.3%) for 1 minute; one (8.3%) for 10 minutes; and one (8.3%) for 30 minutes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations